Cash Transfers Matter! A Critique of the Senate Report on Postsecondary Education - Dean, James M. (Canadian Journal of Higher Education, 1987)
The Standing Senate Committee on National Finance has recently recommended a major change in the way that the federal government provides support to the provinces for postsecondary education. It recommends that the cash transfers under EPF be eliminated and replaced with additional transfers of tax points to the provinces designed to provide the same amount of money. The Committee believes that the current arrangements do not influence the spending priorities of the provinces and such a change would not alter this fact. This paper argues that the Senate Report is based on an economic approach to grants that has been under serious question for 15 years. Both the traditional and the modern theory of grants are discussed. It is argued that there are reasons to believe that a change to the new arrangements would influence provincial spending priorities. Empirical estimates of the change show that provincial governments could be expected to decrease their support for postsecondary education by between $38 to $48 million per year over the next 5 years as a direct result of the proposed change in the way the transfers are made.